ChemInform Abstract: Cross‐Dehydrogenative Coupling for the Intermolecular C‐O Bond Formation. Issue 22 (15th May 2015) - Krylov, Igor B.; Vil', Vera A.; Terent'ev, Alexander O.
Abstract: Review: 303 refs.